2012
DOI: 10.3168/jds.2011-4703
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Pheromonicin-SA affects mRNA expression of toll-like receptors, cytokines, and lactoferrin by Staphylococcus aureus-infected bovine mammary epithelial cells

Abstract: Pheromonicin-SA (Ph-SA) is a newly developed, engineered multidomain peptide that has a bactericidal effect against Staphylococcus aureus. The objective of this study was to characterize innate immune responses by Staph. aureus-stimulated bovine mammary epithelial cells (BMEC) following treatment with Ph-SA. Primary BMEC from one lactating Holstein cow were isolated and exposed to Staph. aureus for 2 h, and then treated with rifampicin or Ph-SA. Total RNA was isolated from BMEC at 0, 2, 6, 12, and 24 h postinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Zhu et al (2012) when exposed primary mammary epithelial cells to Ph-SA found that this compound increases the expression of TLR2, TNF-α, IL-1β, IL-8 and lactoferrin and later the expression of TLR4. Thus, Ph-SA may be value as an antimicrobial in promoting innate immune response by S. aureus aureus-infected bovine mammary epithelial cells, especially regarding the inhibition of innate immune response induced by S. aureus which leads to the chronification of the inflammatory response (Bannerman et al, 2004;Lahouassa et al, 2007;Yang et al, 2008;Motshwene et al, 2009;Guntler et al, 2010;Lin et al, 2010;Lara-Zarate et al, 2011;Schukken et al, 2011;Wellnitz et al, 2012).…”
Section: Therapeutic Opportunitiesmentioning
confidence: 95%
“…Zhu et al (2012) when exposed primary mammary epithelial cells to Ph-SA found that this compound increases the expression of TLR2, TNF-α, IL-1β, IL-8 and lactoferrin and later the expression of TLR4. Thus, Ph-SA may be value as an antimicrobial in promoting innate immune response by S. aureus aureus-infected bovine mammary epithelial cells, especially regarding the inhibition of innate immune response induced by S. aureus which leads to the chronification of the inflammatory response (Bannerman et al, 2004;Lahouassa et al, 2007;Yang et al, 2008;Motshwene et al, 2009;Guntler et al, 2010;Lin et al, 2010;Lara-Zarate et al, 2011;Schukken et al, 2011;Wellnitz et al, 2012).…”
Section: Therapeutic Opportunitiesmentioning
confidence: 95%
“…Primary BMECs were prepared from lactating cows as described previously (17), with some modifications. Briefly, mammary tissue pieces (0.5 to 1 mm 3 ) were transferred into 25-cm 2 cell culture flasks (Corning, Inc., Corning City, NY) and cultured in Dulbecco modified Eagle medium with Ham F-12 nutrient mixture (DMEM/F12; pH 7.2; Gibco, Grand Island, NY) supplemented with 10% fetal bovine serum (Gibco), 100 U of antibiotic (penicillin and streptomycin; Invitrogen, Carlsbad, CA)/ml, 5 g of bovine insulin/ml, 1 g of hydrocortisone/ml, 5 g of progesterone (I8405, H0888, and P8783, respectively; Sigma-Aldrich, St. Louis, MO)/ ml, and 10 ng of murine epithelial growth factor (PeproTech, Rocky Hill, NJ)/ml.…”
Section: Methodsmentioning
confidence: 99%
“…BMECs are poised to respond quickly to pathogen invasion by binding to pathogen-associated molecular pattern molecules via the activation of various pattern recognition receptors (PRRs) (16,17). In general, the binding of a pathogen to a Toll-like receptor (TLR) or nucleotide-binding oligomerization domain (NOD)-like receptor (NLR) activates the MAPK and NF-B signaling cascades, leading to upregulate expression of various proinflammatory cytokines, chemokines, and antimicrobial peptides, thereby triggering inflammation and host immune responses (18).…”
mentioning
confidence: 99%
“…The content of IL-8 has been quantified to evaluate the effect of temperature on bioactive factors in milk (Ramírez-Santana et al, 2012). The mRNA expression of the IL-8 gene in primary bovine mammary epithelial cells as a marker of inflammation has been quantified to evaluate the antibiotic role of a newly developed, engineered multidomain peptide in promoting innate immune responses (Zhu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%